Smart films of carbohydrate-based/sunflower wax/purple Chinese cabbage anthocyanins: A biomarker of chicken freshness. (15th January 2023) - Hashim, Sulafa B.H.; Tahir, Haroon Elrasheid; Lui, Li; Zhang, Junjun; Zhai, Xiaodong; Mahdi, Amer Ali; Ibrahim, Nosyba A.; Mahunu, Gustav Komla; Hassan, Mahmoud M.; Xiaobo, Zou; Jiyong, Shi
Graphic abstract: Highlights: SFW and CPC anthocyanins are well-dispersed in carbohydrate networks. Smart color Films change at various pH, resulting in great food quality indicators. Smart films possess strong UV–vis light protection and vapor barrier properties. SFW enhanced the thermal, mechanical properties and controlled anthocyanin release. Visual biomarker films revealed monitoring the freshness of chicken breast at 25 °C. Abstract: Innovative pH-colorimetric sensor film was fabricated from agar and methylcellulose matrix (AM) with various concentrations of sunflower wax (SFW) (6%, 9%, 12%, and 15% w/w) combined with purple Chinese cabbage (CPC) anthocyanins for tracking chicken breast freshness. A bio-composition film AM/CPC with (hydrophobic) SFW exhibited significant color variations in acidic pH level of (2–6) and a slight shift in alkaline pH levels ranging from (7–12), as well as marked color change due to ammonia vapor. Microstructure analyses revealed that SFW was fixed effectively into the AM-CPC matrices. The incorporation of varying SFW concentrations enhanced the mechanical, thermal, antioxidant activity, reduced anthocyanin release and physical properties (mainly water vapor permeability), with the best performance at AM/CPC/9% SFW. Interestingly, SFW films demonstrated perfect defense opposing UV–vis and visible light. Finally, it was proved that the efficiency of the pH-colorimetric film as an indicator for evaluating the freshness of chicken breast.